LONELINESS IN THE AGE OF ADOLESCENCE AS A SOCIAL AND PSYCHOLOGICAL PROBLEM - Y. V. Zheleznyakova (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Psihologìâ, 2013)
The analysis of the research ?ndings of the contemporary Russian and Ukrainian authors shows  that  there  is  no  consensus  in  interpreting  the  nature  of  loneliness,  its  origin,  speci?c aspects of manifestation in the publications of foreign and native scholars. This allows to outline the problem ?eld of the investigation of loneliness as a social and psychological phenomenon. A teenager acquires social experience in the course of establishing various social relations. The  development  of  individualization,  weakening  of  relationships  with  the  primary  group, intensi?cation of the social mobility within a society and the general instability provoke the growth of the subjective loneliness. The number of teenagers suffering from subjective loneliness grows in the contemporary society. This feeling, as a rule, leads to deviations in behavior and brings about such dangerous consequences as depression, abuse of drugs and alcohol, gambling addiction  and  even  suicide  attempts.  Thus,  loneliness  results  in  serious  problems.  Parental neglect and lack of parental support seem to be the main reasons which stimulate the feelings of loneliness in teenagers. Positive feedback in the families where teenagers experience the lack of parental support is very weak and inadequate, which cause the stagnation of the subsequent socialization of teenagers.